2022
DOI: 10.1108/ijwhm-12-2020-0207
|View full text |Cite
|
Sign up to set email alerts
|

Exploring differences in the subjective well-being of teleworkers prior to and during the pandemic

Abstract: PurposeThis study aims to find out the differences in the employee well-being of teleworkers in Hungary prior to and during the pandemic restrictions and explores whether the differences stem from (1) the presence of children or (2) the changes in the telework situation (freely chosen or forced by pandemic restrictions).Design/methodology/approachAs the first step of this study of office workers, the authors created a “one working day” measure within the conceptual framework of positive psychology that is suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 66 publications
4
18
1
Order By: Relevance
“…Another managerial challenge with remote work was the lack of social relations. To promote the organizational and social work environment some managers increased the amount of communication and support to reduce isolation and loneliness, but also to prevent work overload and overtime, similar to what was noted by Pataki-Bittó and Kun (2022). Working from home may thus include both advantages and risks as found in the study by Ipsen et al.…”
Section: Discussionmentioning
confidence: 77%
“…Another managerial challenge with remote work was the lack of social relations. To promote the organizational and social work environment some managers increased the amount of communication and support to reduce isolation and loneliness, but also to prevent work overload and overtime, similar to what was noted by Pataki-Bittó and Kun (2022). Working from home may thus include both advantages and risks as found in the study by Ipsen et al.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies revealed that among people living in larger households or with a child/children under the age of 12, remote work was associated with family-to-work conflict (Golden et al. , 2006) and lower subjective well-being (Pataki-Bittó and Kun, 2022). Taken together, these findings may indicate that living in larger households or with a child/children under the age of 12 may also have potentially positive effects which can compensate for the negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to our knowledge, no study has explored the impact of perceived insider status (PIS) on the relationship between MAC and SEW. Additionally, until recently, research had seldom focused on the emotional experiences and subjective well-being of employees (Charalampous et al, 2019;Pataki-Bitt o and Kun, 2022). For instance, health professionals have the knowledge, tools, and resources to enhance SEW within changing work conditions, an area needing increased focus (Jeske, 2022).…”
Section: Introductionmentioning
confidence: 99%